Effects of different stocking densities on the CO2 fluxes at water-air interface and the respiration metabolism in sea cucumber Apostichopus japonicus (Selenka) - Mei, Yaoping; Tian, Yuan; Gao, Qinfeng; Dong, Shuanglin; Li, Xueqi; Xu, Yuling (Frontiers in Marine Science, 2022)
Recently, abundant research has been devoted to investigating the variations of CO2 concentration in the atmosphere. However, the information of CO2 fluxes at the water-air interface remains limited, especially those from the respiratory metabolism of aquatic organisms. In the present study, a comprehensive analysis was carried out to evaluate the effects of different stocking densities of sea cucumber (Apostichopus japonicus) on the CO2 fluxes at water-air interface, and to explore the relationships between CO2 fluxes and respiratory metabolism. A total of 60 sea cucumbers were randomly classified into 4 groups with different stocking densities, including 2, 5 and 8 ind./tank (namely D2, D5 and D8 groups). After 34-day feeding trial, individuals in D5 had superior growth performance rather than D2 and D8. The analysis of modified floating static chambers clearly showed that the mean CO2 flux at the water-air interface in D5 was significantly higher than D2 and D8. Meanwhile, energy budget analysis revealed that D5 had higher carbon and nitrogen utilization, excretion energy and metabolizable energy, suggesting relatively active respiration metabolism in moderate stocking density. The activities of pyruvate dehydrogenase (PDH) and α-ketoglutarate dehydrogenase (OGDH) in respiratory tree and body wall tissues provided additional evidence for the higher respiration metabolism rate of individuals at D5, which may be responsible for the higher CO2 fluxes at the water-air interface. Transcriptome analysis was performed to uncover the molecular mechanism of respiratory metabolism affected by different stocking densities. The differentially expressed genes in respiration tree and body wall were significantly enriched in peroxisome, fatty acid degradation, and oxidative phosphorylation pathways. It may explain the differences of respiration metabolism rates at different stocking densities. The present study preliminarily revealed the CO2 fluxes variation at the water-air interface from aquatic invertebrates, and provided the scientific basis for the efficient and low-carbon agricultural technologies of sea cucumber.